Perceptions of diploma holder nurses on continuing higher education: A qualitative study - Anthonysamy, Kaslen; Wan Mamat, Wan Hasliza; Atan, Ashikin; Arini, Merita (Qualitative Research Association of Malaysia, 2024)
Continuing higher education is essential for nurses to adapt to the evolving healthcare landscape. As an essential part of the healthcare system, nurses should pursue further education to broaden their knowledge, develop specialized knowledge, and become experts in their fields. This will promote their professional development and increase their ability to provide high-quality treatment. However, the percentage of registered nurses (RNs) with a degree in Malaysia is still low. Therefore, this study aims to explore the perception of continuing higher education among diploma-holder nurses in Malaysia. A qualitative study was conducted on nine diploma-holder nurses who had extensive experience in public hospitals in Malaysia. Semi-structured interviews were used to collect the data from October 2023 until November 2023. All interviews were recorded, translated, and transcribed verbatim. Thematic analysis was applied to the transcripts for a comprehensive assessment of the gathered data. Two themes were identified concerning nurses’ perceptions of continuing higher education: (1) personal achievement with the following subthemes – a) self-satisfaction and improvement, b) reputation, and c) career pathway, and (2) professional competence in nursing with the following subthemes: a) expanding nursing knowledge, b) self-improvement in patient care, and c) sources of reference. The identified themes on nurses’ perceptions of continuing higher education encompass a multifaceted spectrum. Nurses are highly motivated to pursue higher education, at least to the degree level, to provide better care for patients, enhance their competence, expand their knowledge, and elevate the overall reputation of nursing. As health treatments and care evolve, the motivation to advance the nursing profession through higher education becomes increasingly important for nurses.